Uso da terra nas propriedades rurais de São Miguel Iguaçu localizadas no entorno do Parque Nacional do Iguaçu-PR - Silva, Janice Costa da (2011)
This study aimed to analyze the agricultural activities that occur in the areas surrounding the Iguassu National Park, in the band corresponding to the municipality of São Miguel do Iguaçu. The central focus of the discussion is based on the need for regularization of the use of the natural environment, considered important for environmental conservation. The Iguazu National Park is a conservation of protected areas, where the activities have to comply with its management plan, particularly in the range called the buffer zone (or transition environment) that must have a radius of ten (10) km surrounding the park. That management plan does not allow cultivation of transgenic crops in its buffer zone causing much discussion among the owners. This impediment is discussed and justified by the farmers who criticize the application of these laws. They, in their discussions, they ask that the law is changed, or rather it is licensed for a minimum planting of transgenic crops, which means changing the rules of protection of areas around the National Park. This information subsidize this research, which seeks to facilitate a greater awareness on how to use and exploitation of natural resources, especially close to the environmental reserve, considering the current agricultural techniques that hinder environmental sustainability. At the end of the study it was found that environmental changes, considered more significant in the study area are related to human behavior and economic activities.